Forecasting and modelling the potential cargo throughput of the Northern Sea Route until 2050 - Hellström, Rasmus (My University, 2024)
The cargo volumes of the Northern Sea Route have seen great increases in the past 10–15 years. With the increasing shipping traffic also the negative effects that the traffic has on the Arctic environment are on the increase. Some of these effects include increased CO2 and black carbon emissions, amplified risks for Arctic ecosystems and species, oil spills, and various negative effects on local communities. The effects of black carbon falling on snow and ice are especially devastating, as it can lower the surface albedo dramatically, creating a positive feedback loop which leads to more and more ice and snow melting in the long run. The main research objective of the thesis is to analyse how the potential cargo throughput of the Northern Sea Route is going to evolve until 2050. Additionally, the Arctic environment will be analysed from climatic, environmental, and shipping market point of views. As for the research and modelling methodology, the modelling and forecasting will be done utilizing a capacity model. The cargo capacity of the commercial ice classed cargo vessels as well as the capacity provided by icebreaker support will be modelled separately, with some parameters shared, and some unique to each model. The data is gathered from different databases and sources, and for the sea ice data two CMIP6 models (CNRM-ESM2-1 and NorESM2-MM) are used, both utilizing the SSP370 climate scenario. Both models are operated on a monthly basis, and the timescale of the modelling is until 2050. The results have a lot of yearly variation, and the general level of cargo capacity is very different depending on which climate model is used. For CNRM-ESM2-1, the yearly capacity ranges mostly between 350 and 500 million tonnes, with no clear long-term trend in the capacity. With NorESM2-MM the predicted capacity is much lower, ranging between 50 and 150 million tonnes, with the capacity steadily increasing over time. All of the increase in capacity comes from the icebreakers and not the commercial ice classed cargo vessels, which indicates that the sea ice extent might not decrease too much during the period, but rather the volume and thus average thickness of the ice decreases. In general, the results seem to imply that the capacity for cargo flow is not a constraint at least for now, especially with the results from CNRM-ESM2-1. Instead,the reason for low transit traffic especially is the shipping market not encouraging use of the route compared to other options, such as the Suez Canal Route. For destinational traffic the development of the cargo flow will mostly depend on Russia’s Arctic natural resource projects, along with the hydrocarbon demand in the Asia Pacific market, the construction of the ice fleet, and the modernization of port infrastructure in the Arctic. However, as there are so many uncertainties and assumptions present in the capacity models, the level of capacity depicted by both climate models is more of a theoretical maximum, than a likely actual level. For future research, modelling and estimating the emissions that could be possible with full utilization of the potential cargo throughput of the Northern Sea Route is one possibility. Further research from here could include analysis of the effects that the potential emissions could have on the Arctic climate and environment.

Pohjoisreitin rahtimäärät ovat kasvaneet huomattavasti edellisen 10–15 vuoden aikana. Lisääntyvän rahtiliikenteen myötä myös liikenteen negatiiviset vaikutukset arktiseen ympäristöön ovat kasvussa. Näitä negatiivisia vaikutuksia ovat esimerkiksi kasvavat CO2- sekä mustahiilipäästöt, voimistuneet riskit arktisille ekosysteemeille ja lajeille, öljyonnettomuudet, sekä muut negatiiviset vaikutukset paikallisille yhteisöille. Mustahiilipäästöjen vaikutukset ovat lumelle ja jäälle pudotessaan erityisen haitallisia, koska se voi laskea näiden pintojen albedoa huomattavasti, luoden positiivisen takaisinkytkennän, joka johtaa entistä nopeampaan jään ja lumen sulamiseen. Tämän työn päätutkimusongelmana on selvittää, miten Pohjoisreitin potentiaalinen rahdinläpäisykyky tulee kehittymään vuoteen 2050 saakka. Lisäksi arkista aluetta analysoidaan ilmastollisesta, ympäristöllisestä, sekä kuljetustaloudellisesta näkökulmasta. Ennustaminen ja mallinnus toteutetaan eräänlaisella kapasiteettimallilla, jossa jääluokallisten kaupallisten alusten rahtikapasiteetille sekä jäänmurtoavun rahtikapasiteetille luodaan omat mallit. Mallien välillä osa parametreista on samoja, osa uniikkeja kuhunkin malliin. Data kerätään erilaisista tietokannoista sekä muista lähteistä, ja jäädata on peräisin kahdesta CMIP6-mallista (CNRM-ESM2-1 ja NorESM2-MM), joissa molemmissa mallinnus seuraa SSP370 ilmastoskeenarioa. Molemmat mallit toimivat kuukausitasolla, ja mallinnuksen aikaväli on vuoteen 2050 saakka. Tuloksissa on paljon vuosittaista vaihtelua, ja rahtikapasiteetin taso on hyvin erilainen riippuen siitä, kumpaa ilmastomallia seurataan. CNRM-ESM2-1:n kohdalla vuosittainen kapasiteetti vaihtelee enimmäkseen 350 ja 500 miljoonan tonnin välillä, eikä kapasiteetin kehityksessä ole nähtävissä pitkäaikaisia trendejä. NorESM2-MM:n kanssa ennustettu kapasiteetti on paljon matalampi, vaihdellen enimmäkseen 50 ja 150 miljoonan tonnin välillä, ja lisäksi kapasiteetti kasvaa ajan myötä. Kapasiteetin kasvu johtuu jääluokallisten kaupallisten rahtialusten sijaan jäänmurtajien kapasiteetin kasvusta, joka implikoi sitä, että merijään ulottuvuus ei välttämättä laske tarkastelujaksolla kovinkaan paljon, vaan ennemminkin jään tilavuus ja näin keskimääräinen paksuus laskevat. Yleisesti ottaen tulokset vaikuttuvat implikoivan sitä, että Pohjoisreitin rahtikapasiteetti ei ainakaan toistaiseksi toimi pullonkaulana rahdin virtaamiselle. Syynä matalalle kauttakulkuliikenteelle on ennemminkin se, että kuljetusmarkkinat eivät kannusta reitin käyttöön muihin vaihtoehtoihin, kuten Suezin kanavaan, verrattuna. Määränpääliikenteen osalta rahtimäärien kehittyminen tulee riippumaan enimmäkseen Venäjän arktisen alueen luonnonvaraprojekteista, näiden luonnonvarojen (kuten maakaasun ja öljyn) kysynnästä Aasian ja Tyynenmeren alueella, jääluokallisten alusten rakentamisesta, sekä arktisen alueen satamainfrastruktuurin modernisoinnista. Toisaalta kapasiteettimallit sisältävät paljon epävarmuuksia ja oletuksia, joten niiden ennustamaa kapasiteettia voidaan pitää ennemminkin teoreettisena maksimina, kuin todennäköisenä todellisena tasona. Jatkotutkimuksen kannalta yhtenä vaihtoehtona olisi mallintaa ja ennustaa päästöjä, joita Pohjoisreitin potentiaalisen rahdinläpäisykyvyn täysi hyödyntäminen mahdollisesti tuottaisi. Tästä olisi edelleen mahdollista jatkaa analyysia näiden päästöjen vaikutuksiin arktisen alueen ilmastoon sekä ympäristöön.
Keywords: Potential cargo throughput, cargo capacity, cargo volume, shipping traffic, Northern Sea Route, Northeast Passage.